Kajian Kriminologi Terhadap Tindak Pidana Mafia Tanah - Harahap, Anissa Aldawiah; Ramadhani, Rahmat (Universitas Muhammadiyah Sumatera Utara, 2024)
Criminology is a science that studies crimes or violations of law by legal subjects, where the law that is violated results in a reaction from the law itself. As Sutherland defines criminology is the processes of making laws, violating laws. The research method used is normative juridical research, namely legal research carried out by examining library materials or secondary data. The land mafia is a conspiracy between parties with evil intentions in controlling land and the participation of officials who have the authority to issue the legality of land rights. Land rights are basically created by the right to control the state as a constitutional command, Article 33 paragraph (3) of the 1945 Constitution, states;